Hematological Changes in Patients of Chronic Renal Disease and Their Response to Treatment with Erythropoietin - Asif, Naghmi; Hasan, Sadaf; Hassan, Khalid (International Journal of Pathology, 2018)
Introduction: Anemia is a common manifestation of chronic kidney disease, especially when the glomerularfiltration rate falls below 30 ml/min. For evaluation of anemia, it is important to exclude othercauses of anemia such as iron and other hematinic deficiencies, chronic inflammation or the effect ofdrugs. After reversible causes of anemia are excluded, supplementary erythropoietin (EPO) can be consideredwhen the patient's haemoglobin concentration falls below 11 g/dl.Methodology: This prospective study was conducted at Nephrology unit of Holy Family Hospital Rawalpindi,from April- June 2014. Fifty diagnosed patients of chronic kidney disease presenting withanemia were included in the study. Their CBC was done on Sysmex KX21 to check their baseline parameters.About 4000 iu of EPO was administered subcutaneously to all patients for three weeks andCBC was done at the start of 4th week. Results were entered on SPSS version 17 for further analysis. Pvalue of < 0.05 was taken as statistically significant.Results: Total number of cases included during the study period was 50. Their age range was between13-68 years with the mean age of45.1+1.64 SD. Among these 28 (56%) were males and 22 (44%) werefemales. Changes in hematological parameters in CKD patients were noted. Notable changes were seenonly in Hemoglobin levels. Mean Hemoglobin before the start of treatment was 8.10gms/dl + 0.107SDwhereas after treatment mean hemoglobin increased to 8.93 + 0.100 SD with highly significant p valueof 0.000. MCH also showed a significant improvement with a mean MCH (before treatment) 31.43 +0.048 SD to mean MCH of 31.73+0.058 (after treatment) with a significant p value of 0.000. Changes inother hematological parameters were insignificant.Conclusion: Among hematological parameters hemoglobin is the most commonly affected. Erythropoietinplays an effective role in increasing hemoglobin level in these patients.